CONTRIBUTION OF INTERNATIONAL RECOGNITION THROUGH SUKUK INVESTMENT INTEREST IN GENERATION Z - Imro’ah, Wulidatul; Safitri, Rini (Faculty of Economic and Business, University of Pasundan, 2024)
Sukuk investment is significant in overcoming financial problems in the future and has an impact on global financial markets. This study aims to determine the contribution of international recognition through Sukuk investment interest among Generation Z by examining the effect of financial literacy and financial management behavior on Sukuk investment interest, with lifestyle as a moderating variable. This research uses a quantitative approach with primary data type. The sampling technique applies a non-probability sampling method with a purposive sampling type to obtain 400 respondents. Data analysis and hypothesis testing in this study apply the Structural Equation Model-Partial Least Squares (PLS-SEM), with the software used in the form of Ms. Excel and Smart PLS. Based on the analysis, the results show that the financial literacy of Generation Z has a positive and significant effect on Sukuk's investment interest. Additionally, the financial management behavior of Generation Z has a positive and significant effect on Sukuk's investment interest. Furthermore, lifestyle can moderate the impact of financial literacy on Sukuk investment interest but cannot reconcile the effect of financial management behavior on investment interest.